The Effect of Paired Short Pass and Goal Target Short Pass Training on Students' Short Pass Ability at SMA Negeri 1 Kecamatan Payakumbuh - Amrina Rabilla; Putra, Yogi Arnaldo; Roma Irawan; Bram Sujadesman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study tried to find out how much paired short pass training and goal target short pass training can improve students' short pass skills, and also to see which method works better. The study used an experimental approach with two groups, measuring their performance before and after the treatment. The group included 33 students from SMA Negeri 1 Kecamatan Payakumbuh, and they were split into two groups, each with 16 students. The research tool was a brief test measuring passing skills given before and after the training program. The data were looked at using several statistical methods, including descriptive statistics, a Shapiro–Wilk test to check for normal distribution, a Levene's test to see if variances were similar, and two types of t-tests—paired-samples and independent-samples—to compare groups.All of this was done using the Jamovi software. The results showed that training focused on short passing goals greatly improved students' short passing skills, with the average score going up from 3.88 to 5.13 (t = -4.23, p < 0.001). When students did paired short pass training, their ability to make short passes improved a lot.The average score went up from 4.00 to 5.81, which is a big difference.This result was statistically significant, with a t-value of -6.54 and a p-value less than 0.001. The independent-samples t-test showed that there was no significant difference in how well the two training methods worked (t = -1.10, p = 0.281). Although the group that practiced paired short passes showed a greater average improvement compared to the group that focused on goal-targeted short passes, the difference wasn't big enough to be considered statistically significant. Both training methods work well at helping students improve their short passing skills, but one isn't much better than the other.